Pengaruh Model Problem Based Learning Berbantuan Media Digital Kahoot Terhadap Pemahaman Konsep Matematis Peserta Didik Kelas V SD Mujahidin Pontianak - Marwa Marwa; Hery Kresnadi; Rio Pranata (Departement of Mathematics Education, 2023)
This study aims to analyze the effect of problem-based learning model assisted by kahoot digital media on mathematical concept understanding of fifth grade students of SD Mujahidin Pontianak. The method used was an experiment with the form of Quasi-Esperimental Design with the type of non-equivalent control group design. The population was all fifth grade students consisting of 5 classes. The samples of this study were VB class students totaling 29 students and VD class students totaling 27 students. The data collection technique used is the measurement technique and the data collection tool is a written test in the form of multiple choice. Based on data analysis, the average results of the final test of the experimental class were 75.82 and the average final test of the control class was 65.94. the results of hypothesis testing using t-test (separated variance) obtained tcount = 3.337, while for dk (27+28-2 = 54) with a significant level α = 5% obtained ttable = 1.673565 which means tcount > ttable, then accepted, this proves that there is an effect of the problem-based learning model assisted by kahoot digital media on understanding mathematical concepts. Based on the results of the calculation of effect size (ES), ES = 0.81 is obtained which is included in the high criteria. Thus it can be concluded that the problem-based learning model assisted by kahoot digital media has a positive influence on the understanding of mathematical concepts of fifth grade students of SD Mujahidin Pontianak.